2016
DOI: 10.5369/jsst.2016.25.4.247
|View full text |Cite
|
Sign up to set email alerts
|

MPTMS Treated Au/PDMS Membrane for Flexible and Stretchable Strain Sensors

Abstract: Au/PDMS membranes are widely used to fabricate strain sensors which can detect input signals. An interfacial adhesion between metal films and polydimethylsiloxane (PDMS) substrates is one of the important factors determining the performance of strain sensors, in terms of robustness, reliability, and sensitivity. Here, we fabricate Au/PDMS membranes with (3-mercaptopropyl) trimethoxysilane (MPTMS) treatment. PDMS membranes were fabricated by spin-coating and the thickness was controlled by varying the spin rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, the problems of weak metal adhesion due to low surface energy and PDMS thermal expansion due to the baking step of the photolithography still remain unresolved. It has been demonstrated that stable metal deposition is possible by improving the PDMS surface energy through plasma [35], 3-aminopropyltriethoxysilane (APTES) [36], 3-mercaptopropyltrimethoxysilane (MPTMS) [37], and 3-isocyanatopropyltriethoxysilane (IPTES) [38], but structural damage due to thermal expansion cannot be prevented [39].…”
Section: Resultsmentioning
confidence: 99%
“…However, the problems of weak metal adhesion due to low surface energy and PDMS thermal expansion due to the baking step of the photolithography still remain unresolved. It has been demonstrated that stable metal deposition is possible by improving the PDMS surface energy through plasma [35], 3-aminopropyltriethoxysilane (APTES) [36], 3-mercaptopropyltrimethoxysilane (MPTMS) [37], and 3-isocyanatopropyltriethoxysilane (IPTES) [38], but structural damage due to thermal expansion cannot be prevented [39].…”
Section: Resultsmentioning
confidence: 99%